Unraveling the multiple interactions between phages, microbes and flavor in the fermentation of strong-flavor Baijiu - Huadong Zhang; Hongxia Zhang; Hai Du; Yan Zhang; Menghui Zhang; Xiaowei Yu; Yan Xu (Bioresources and Bioprocessing)
Abstract The fermentation process of strong-flavor Baijiu represents a complex and unique ecosystem, characterized by the involvement of various microorganisms that drive intricate biochemical reactions, ultimately contributing to the distinct flavor profile of the Baijiu. Viruses may affect the succession of microorganisms and thus affect the style and quality of the product. However, the interaction between viruses and microorganisms during the fermentation of Baijiu is still unclear. Here we combined viral metagenomics and amplicon sequencing, physicochemical analysis, and GC–MS detection with temporal sampling to study the dynamics of viral and microbial communities, physicochemical properties, and flavor compounds during strong-flavor Baijiu fermentation. Viral metagenomic analysis revealed 513 viral operational taxonomic units (vOTUs), encompassing 34 viral families. Principal coordinates analysis (PCoA) demonstrated significant differences in vOTUs at different fermentation stages. Notably, the microbial community exhibited distinct succession patterns at various fermentation stages; it changed rapidly during the initial five days, with similarities observed between days 10 and 20. Volatile profile analysis identified 38 flavor components in fermented grains, comprising 16 ester compounds, 11 alcohols, and 8 acids, with the majority formed between days 10 and 30. The Spearman's rank correlation analysis revealed that Peduoviridae exhibited a negative correlation with Gluconobacter. Genomoviridae showed a negative correlation with Issatchenkia, Penicillium, and Monascus. These findings highlight the potential for complex interactions between viruses and microbial communities during Baijiu fermentation, underscoring the importance of considering viral communities in studies of the microbial ecology of fermented foods. Graphical Abstract